Seismic Behavior of Turbine-Generator Foundation under Strong Earthquake Action in Different Directions - Dong An; Tie-jun Qu (Advances in Civil Engineering)
In order to study seismic behavior of half-speed turbine-generator foundation under horizontal earthquake loading in different directions, the 1/10 scaled model was designed and fabricated. The rigid foundation of half-speed turbine-generator sets can be seen as a complex space frame system. The tests were conducted under eight earthquake waves in two directions separately. The loading directions were along the axis of longitudinal and transverse. The seismic response of displacement and story drift was investigated by a pseudodynamic test. The hysteresis behavior and crack propagation were analyzed. From the research, it is shown that the maximum displacement of the foundation under the earthquake of intensity 7 is 15.20 mm (longitudinal), basically in the range of elastic deformation. The seismic response of earthquake input in different directions is obviously different. Under the same earthquake input, the seismic displacement along the axis of longitudinal is larger than that of transverse. Under the rarely earthquake of intensity 8, the foundation still keeps good working condition. The maximum elastic-plastic story drift is 1/191 under the limit value 1/50 provided in the Code for Seismic Design of Buildings. The deformation capacity of the structure meets the requirements of the current seismic design code of China.